Novel EYA1 variants causing Branchio-oto-renal syndrome - ELÇİOĞLU, HURİYE NURSEL (ELSEVIER IRELAND LTD, 2017)
Introduction: Branchio-oto-renal (BOR) syndrome is an autosomal dominant genetic disorder characterized by second branchial arch anomalies, hearing impairment, and renal malformations. Pathogenic mutations have been discovered in several genes such as EYA1, SIX5, and SIXI. However, nearly half of those affected reveal no pathogenic variant by traditional genetic testing. Methods and materials: Whole Exome sequencing and/or Sanger sequencing performed in 10 unrelated families from Turkey, Iran, Ecuador, and USA with BOR syndrome in this study. Results: We identified causative DNA variants in six families including novel c.525delT, c.979T > C, and c.1768deIG and a previously reported c.1779A > T variants in EYA1. Two large heterozygous deletions involving EYA1 were detected in additional two families. Whole exome sequencing did not reveal a causative variant in the remaining four families. Conclusions: A variety of DNA changes including large deletions underlie BOR syndrome in different populations, which can be detected with comprehensive genetic testing. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Branchiootorenal syndrome; EYA1; Branchial arch anomalies; Hearing loss; Whole exome sequencing; BOR SYNDROME; HEARING-LOSS; CHROMOSOME 8Q; GENE; LOCALIZATION; DISEASE; LINKAGE; FAMILY; REGION; EAR